IMPLEMENTASI ALGORITMA BASE-64 DALAM MENGAMANKAN URL (UNIFORM RESOURCE LOCATOR) WEBSITE LAYANAN PENGADUAN MASYARAKAT DESA BOJONGRAHARJA - Taufiq Hidayatullah (Jurnal Media Infotama, 2022)
URL (Uniform Resource Locator) is an address that stores data or information that is directly related to the website. In general, the benefit or function of a URL is to identify the address of the data stored by the website, either in the form of image data or numbers that will be displayed on the website page. At the web URL, there is often a crime of data theft or hacking of the web display itself which is often called a Deface Website where people who are not responsible for committing these crimes look at the security of the web itself. To prevent this crime attack, the URL of the website utilizes the security of the science of cryptography, namely using the Base64 flowchart is used. In the software development process using the PHP programming language (Hypertext Preprocessor), and coupled with HTML, CSS, JavaScript. For writing or coding the program using Sublime Text, the last one is to store the database using MySQL, in testing the level of security using the WebCruiser WebVulnability Scanner. In the application of the Base64 algorithm, it is certain that the URL can be encrypted properly so it will be safe, so the website will be safe from attacks by bad people who are not responsible for stealing data or deface the website.